2017
DOI: 10.1073/pnas.1708853114
|View full text |Cite
|
Sign up to set email alerts
|

Generating gradient germanium nanostructures by shock-induced amorphization and crystallization

Abstract: Gradient nanostructures are attracting considerable interest due to their potential to obtain superior structural and functional properties of materials. Applying powerful laser-driven shocks (stresses of up to one-third million atmospheres, or 33 gigapascals) to germanium, we report here a complex gradient nanostructure consisting of, near the surface, nanocrystals with high density of nanotwins. Beyond there, the structure exhibits arrays of amorphous bands which are preceded by planar defects such as stacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 41 publications
(32 reference statements)
0
16
2
Order By: Relevance
“…The previous claim of shock-induced amorphization of Ge, based on an examination of recovered laser-shocked Ge samples [29], is contradicted by our results. The crystallization to the cd phase from the shocked state (lacking long range order) observed in our in situ measurements, upon uniaxial strain stress release, indicates that the shocked Ge was liquid rather than a metastable amorphous phase.…”
Section: Recent Experimental Advances Utilizing New Xrd Capabilities contrasting
confidence: 99%
See 1 more Smart Citation
“…The previous claim of shock-induced amorphization of Ge, based on an examination of recovered laser-shocked Ge samples [29], is contradicted by our results. The crystallization to the cd phase from the shocked state (lacking long range order) observed in our in situ measurements, upon uniaxial strain stress release, indicates that the shocked Ge was liquid rather than a metastable amorphous phase.…”
Section: Recent Experimental Advances Utilizing New Xrd Capabilities contrasting
confidence: 99%
“…Recent preliminary XRD measurements in laser shocked Ge suggested a solid-solid transition precedes melting [28]; because the focus was to demonstrate simultaneous phase contrast imaging (PCI) and XRD measurements, neither the transition stresses nor the structure of high-pressure crystalline phase(s) were reported. In contrast, analysis of recovered Ge samples, laser shocked to ~33 GPa, and classical molecular dynamics (MD) simulations have reported that Ge amorphized under shock compression [29]. However, these results require further examination because time-scales of MD simulations and recovery experiments differ by many orders of magnitude.…”
Section: Recent Experimental Advances Utilizing New Xrd Capabilities mentioning
confidence: 99%
“…According to the results reported in References [ 34 , 35 , 36 , 37 ], the crystal-to-amorphous transition can be attributed to the local temperature rising to the melting point of the material due to plastic deformation and its subsequent fast cooling. Worswick and Yang [ 38 ] assumed that 5% of the plastic deformation work was stored in the grain defects and 95% was transformed into heat.…”
Section: Resultsmentioning
confidence: 97%
“…Similar results and formation mechanisms were reported by Wang et al [ 34 ], who found that the threshold peak pressure for amorphization of a NiTi alloy was about 3.3 GPa (the pressure is 4.4 GPa in this case). Meyers [ 35 , 36 ] found that shear bands were generated in AISI 304 stainless steel and germanium under shock loading conditions, and the formation of an amorphous phase was observed in these shear bands. The liquid-solid structure induced by the local temperature rising and subsequent fast cooling were the main reasons for the formation of an amorphous phase; however, the LSP-induced surface amorphization of titanium alloys has not been reported in the literature so far.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the development of high power pulsed lasers, high amplitude (10s to 100s of GPa) shock wave with ns pulse duration can be produced, which enables the exploration of materials science in this unknown regime. In this investigation, we have successfully shock recovered four different brittle materials, namely, Si [5][6], Ge [7], B 4 C [8], and SiC, all of which are covalently bonded.…”
Section: Introductionmentioning
confidence: 99%